To where Is China running? Challenges and perceptions after 40 years of Chinese reforms, transformation, and integration into the world economy - Bahri Yılmaz (Koç University-TÜSİAD Economic Research Forum (ERF), 2019)
If we look at the last four decades, without any doubt we can argue that China is the rising economic power of the 21st century, which may be called the Chinese Century. It is an economic miracle but not an economic mystery. In 2018, China celebrated the 40th anniversary of reform and opening to global trade. Since 1978, the country has transformed from one of the poorest low-income countries to one of the three leading economies in the world. The country has changed from an agricultural-led economy to an industrial one and from a purely command economy to a world market-oriented economy. The country accounts for one-third of global growth. Over 800 million people have been carried over the poverty line, and many in China have reached upper middle-class status. This paper has been divided into three parts. In the first part, we will discuss the economic performance of China and its place in the world economy from 1978 until today. In the second part, we will examine the major macroeconomic problems China faces in the beginning of 2019. In the last part, we will draw some conclusions with regard to China's main external and internal challenges and make some recommendations for solutions to China's economic problems.
Keywords: 330